2020
DOI: 10.1186/s12889-020-8183-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between self-compassion and self-rated health in 26 samples

Abstract: Background: Although there is growing evidence of the relevance of self-compassion for understanding health outcomes, few studies have examined self-compassion in relation to self-reported physical health status, also known as self-rated health (SRH). This study addressed this gap by examining the associations between selfcompassion and SRH across multiple samples and after accounting for the contributions of positive and negative affect. Methods: Data from 26 samples (total N = 6127), comprised of 6 universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Bombak, 2013). This scale was also found to be reliable and valid across a wide range of ages, and suitable in epidemiologic studies for different populations (Miilunpalo et al, 1997;Sirois, 2020). Similarly, the scale which was translated into Hebrew was found to be an effective measure in several diverse contexts (Anaby et al, 2010;Carmel et al, 2007).…”
Section: Measurementsmentioning
confidence: 80%
“…Bombak, 2013). This scale was also found to be reliable and valid across a wide range of ages, and suitable in epidemiologic studies for different populations (Miilunpalo et al, 1997;Sirois, 2020). Similarly, the scale which was translated into Hebrew was found to be an effective measure in several diverse contexts (Anaby et al, 2010;Carmel et al, 2007).…”
Section: Measurementsmentioning
confidence: 80%
“…We assessed subjective well-being using the Self-rated Health (SRH) item (Ware and Sherbourne, 1992). The SRH is a widely used, well-validated, and reliable measure of subjective health and overall physical well-being (Sirois, 2020). It is a predictor of several important health-related outcomes, including cortisol responses to stress, morbidity, and mortality.…”
Section: Physical Well-beingmentioning
confidence: 99%
“…While studies in this field often focus on a more general relationship between self-compassion, compassion fatigue, and burnout syndrome among healthcare professionals [ 28 ] or between self-compassion and well-being in medical students [ 29 ], our pilot study describes a new specific association between self-compassion and the “good doctor” concept. Following other studies [ 18 , 30 – 33 ], our partial results could contribute to the discussion of the meaningfulness of educational interventions for medical students that develop self-compassion, such as mindfulness-based programs [ 34 36 ]. Although our current results look promising and open a relatively new question in this area, an essential part of the future work will entail incorporating other psychological concepts such as self-criticism, perfectionism, stress, shame and guilt and self-esteem.…”
Section: Discussionmentioning
confidence: 54%
“…Weingartner and colleagues [ 17 ], in their Compassion Cultivation Training for medical students, showed that this kind of program is able to influence students’ self-compassion. Self-compassion has been associated with self-rated health in university students [ 18 ]. Self-compassion has been identified as a transtherapeutic and transdiagnostic phenomenon that plays a role in developing and maintaining mental health and quality of life [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%